Microelements in the slope agricultural landscape of the Central Blackearth Region and their correlation with grain crop productivity - O. A. Mitrokhina (Зерновое хозяйство России)
The purpose of the current study was to determine the content of mobile forms of microelements in soils with different relief and to establish the correlation between elements and productivity of the main agricultural crops under the conditions of the Central Blackearth Region. The study was carried out on the territory of the Kursk region on the fields of the FSBSI Kursk FARC in the laboratory for agrochemistry and agroecological monitoring in the period from 2006–2016. The subjects of the study were microelements and their quantity. The object of the study was the arable soil and grain crop productivity. There has been established that the slopes of polar exposures have different levels of microelement content. The content of mobile copper has decreased on the slope of the northern exposure and amounted to 0.07 mg/kg and 0.09 mg/kg on the watershed plateau. On the slope of the southern exposure, it has tended to increase (0.10 mg/kg). The highest content of mobile zinc has been determined on the watershed plateau (0.13 mg/kg), the lowest on the southern slope (0.06 mg/kg). The manganese content on the territory of the watershed plateau was relatively higher in comparison with the slopes of polar exposures (17 mg/kg), northern slope (10.8 mg/kg), and southern one (8.0 mg/kg). There has been found that microelements have a different effect on productivity of the studied grain crops according to land relief. On the territory of the northern slope and the watershed plateau, barley productivity has been more influenced by the content of zinc and manganese. Winter wheat productivity was dependent on manganese. On the southern slope, productivity of the studied grain crops was significantly affected by both the content of mobile zinc and manganese.